Inflationary effects on professors' quality of life: an analysis at Bahia state universities (Revista Contexto & Educação, 2026)
This article aims to analyze the perceptions of education professionals within the state higher education system of Bahia regarding the effects of inflation on teaching quality of life. It presents survey research with 236 responses from four universities in Bahia. The study employed exploratory factor analysis, multiple linear regression models, and classification and regression trees to examine various constructs. These constructs include quality of life, salary adjustments, salary policies, consumption baskets, training expenses, health, leisure, scientific dissemination, and a sense of justice. The results indicate that the analyzed group experiences a low level of quality of life and that inflation negatively affects their perception of quality of life.
Keywords: inflationary effects; quality of life; university professors